Coming together to improve access to medicines: The genesis of the East African Community's Medicines Regulatory Harmonization initiative. - Hiiti Sillo; Aggrey Ambali; Samvel Azatyan; Chimwemwe Chamdimba; Eliangiringa Kaale; Joseph Kabatende; Murray Lumpkin; Jane H Mashingia; David Mukanga; Bonaventure Nyabenda; Gordon Sematiko; Margareth Sigonda; et al. (PLoS Medicine)
Hiiti Sillo and colleagues reveal how the East African Community's Medicines Regulatory Harmonization initiative improves access to important medicines in Africa.